Public opinion survey on the issues of interests for the provincial people's councils of Hai Phong, Nghe An and Binh Duong on the request and supported by the VIE/98/HO1 Project. Executive summary - Center for Public Opinion survey; Center for Public Opinion survey (Center for Public Opinion survey. Department of Ideology and culture. Communist Party of Vietnam, 2001)
To explore the opinions of the PC's deputies on the issues relating to the functioning of PCs. Based on the findings of the survey, to identify the problems and constraints arisen during decision making process and to propose recommendations. To standardize the procedure of a sociological public opinion survey to serve the needs of PCs and to transfer the survey techniques to the relevant unit of the Office of National Assembly